Pengaruh Profitabilitas, Kepemilikan Manajerial dan Leverage Terhadap Manajemen Laba Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Herman Wijaya; Linda Utami; Wiwin Arifin; Burhanudin (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This study aims to examine the effect of profitability, managerial ownership, and leverage on earnings management with company size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2022. The research method used is a quantitative method employing multiple linear analysis and MRA, with data processed using SPSS version 25. The population of this study consists of 140 manufacturing companies listed on the IDX for the period 2017-2022, and a sample of 53 companies with a total of 318 company data points was obtained. The sample was selected using purposive sampling based on specific criteria. The results of the study indicate that profitability, managerial ownership, and leverage significantly affect earnings management. Company size does not moderate the effect of profitability, managerial ownership, and leverage on earnings management